BIOLOGICAL ASSET INTENSITY, COMPANY SIZE, GROWTH, OWNERSHIP CONCENTRATION, AND TYPE OF PUBLIC ACCOUNTANT FIRM AGAINST BIOLOGICAL ASSET DISCLOSURE - Istutik, Istutik; Navisha, Ainun (Universitas Tidar, 2021)
This study aims to examine and analyze the effect of biological asset intensity, company size, company growth, ownership concentration, and type of public accounting firm on biological asset disclosure in agricultural companies listed on the Indonesia Stock Exchange 2016-2018. This study used purposive sampling in determining the sample and obtained 57 samples. The analytical method used is multiple linear regression analysis. The results of this study indicate that biological asset intensity and company size have a positive effect on biological asset disclosure. Company growth and ownership concentration have a negative effect on biological asset disclosure. Meanwhile, the type of public accounting firm has no effect on the biological asset disclosure.